Blooming calendar and polliniferous plants in Djuanda Great Forest Park, West Java, Indonesia: Implication for beekeeping management - TEGUH HUSODO; INDRI WULANDARI; YOLANI SYAPUTRI; HIKMAT KASMARA; WAWAN HERMAWAN; JOKO KUSMORO; SYA SYA SHANIDA; FADIAH KHAIRINA; M. RIFKY ALIF HAYDAR; M. NAUFAL ASYRAF; RIFKY ROCHIMAT FEBRIAN (Society for Indonesian Biodiversity, 2024)
Abstract. Husodo T, Wulandari I, Saputri Y, Kasmara H, Hermawan W, Kusmoro J, Shanida SS, Khairina F, Haydar MRA, Asyraf MN, Febrian RR. 2024. Blooming calendar and polliniferous plants in Djuanda Great Forest Park, West Java, Indonesia: Implication for beekeeping management. Biodiversitas 25: 3216-3229. Information was unavailable regarding the types of pollinator plants and their blooming periods in Djuanda Great Forest Park, West Java, Indonesia. Information about flower blooming seasons was useful for various purposes. These findings will provide a basis for understanding the importance of Apis cerana Fabricius, 1793 in plant pollination and plant species resources for honey bees so that beekeeping practices can be carried out sustainably. The blossoming period of a plant is determined by its blooming period at the time of observation. The blooming period is observed every month in the second and fourth weeks for six months (December 2021-May 2022). Pollen collection was carried out in August 2021 (dry season). Pollen identification was carried out using the acetolysis method, which involves dissolving the non-pollen components of a sample to reveal the pollen grains, thereby enabling accurate identification. An overview of the observation records revealed the presence of 249 plant species from 82 families. The Asteraceae family has the most abundant species richness. Most plants were identified as pollinator plants (30.52%), nectariferous plants (10.04%), and plants that produce both (18.47%). Flowering plants of melliferous plants for honeybees are available throughout the rest of the year, especially from December to May. Therefore, to optimize honey harvesting, it is important to establish multiple colonies during periods of large honey flows. Honeybees may use alternative sugar sources beekeepers provide, such as fruit juice, during nectar scarcity. We would like to know more about the year-round bloom calendar. Sharing knowledge with farmers about the availability of melliferous plants in certain months will empower them to make decisions for sustainable beekeeping.